Design of Information System for Acceptance Selection of Prospective Employees Online Using Tahani Fuzzy Logic Method and Simple Additive Weighting (SAW) - Bedi Supriaty; Rheo Malani; Oki Dwi Nurhayati (International Journal of Computing and Informatics (IJCANDI), 2016)
applicant selection system by using Tahani fuzzy logical method and Simple Additive Weighting (SAW). This research is designed due to the job applicant selection system that hasn’t been optimized so that the management of an institution as well as a company faces some difficulties and barners in selecting the perfect human resources to be hired. The method applied in this research are Tahani fuzzy logical method and Simple Additive Weighting (SAW) producing web application-based software system that can handle the job applicant selection process by analyzing the data of job application as well as job applicant’s data. This kind of system produced some outputs consisting of job-applicant candidate rank, ideal job applicant rank, and also final rank.